One‐Pot Synthesis of α‐Amino Nitrile Units through Alkylative Strecker Cyanation from Formamides. Issue 25 (6th July 2021) - Yu, Bao; Bodinier, Florent; Saague‐Tenefo, Maximiliene; Gerardo, Patrice; Ardisson, Janick; Lannou, Marie‐Isabelle; Sorin, Geoffroy
Abstract: In this work, we describe the one‐pot synthesis of α‐amino nitrile units by the concomitant addition of alkyl (or aryl) Grignard reagents and TMS cyanide through alkylative Strecker cyanation from readily available formamides. The reaction is broad in scope and the conditions are mild, inexpensive, and easy to set‐up, providing numerous α‐amino nitriles in good yields (34 examples, 41–94 % yield). Abstract : Easy and straightforward access to α‐amino nitrile units by one‐pot synthesis through a reductive Strecker cyanation from readily available formamides. The reaction is broad in scope and the conditions are mild, inexpensive, and easy to set‐up, providing numerous α‐amino nitriles in good yields (34 examples, 41–94 % yield).